Covid-19, Clinical Manifestations in Pregnant Women, Aftermaths on Timing and Mode of Delivery at Hail, Saudi Arabia - Nuzhat Parveen, Mohammed Salem M Alharbi, Razan Fahad Abdullah Alzamil, Shuruq Radhi Ali Al Rashdi, Aryam Fatim Sayfi Alharbi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The study was performed to identify the clinical manifestation of Covid-19 infection during pregnancy its impact on the pregnancy outcomes, and its presentation in completely/incompletely vaccinated women. Material and Methods: We conducted this cross-sectional study at Ha`il, a northern city in Saudi Arabia, starting from 15th Dec. 2021 till 15th Jan. 2022. The mean differences of background variables were computed by using the Independent-Sample t-test. A Chi-square test was applied to assess the presentation of the disease in pregnant/non–pregnant and vaccinated/ non-vaccinated women. P-value <0.05 was taken as statistically significant. Results: Fatigue followed by fever and cough (65, 42, and 38% respectively) were the most common presentations of infection during pregnancy. Hospitalization (15.4%) and ICU (9.4%) admissions were more in pregnant than in non-pregnant women. Clinical manifestations were the same in the completely and incompletely vaccinated women. The incompletely vaccinated women were at increased risk of hospitalization (p-value 0.01), and pneumonia (p-value 0.05). The covid-19 infection has no significant association with age of the participants, body mass index, and parity. Covid-positive women during pregnancy underwent fewer cesarean- sections than Covid negative (20% vs. 80%, p <0.05). The mean gestational age at delivery, preterm birth, and neonatal weight at birth were the same in both groups. The rate of transmission of the infection to the neonates remained extremely low. Conclusion: Covid disease during pregnancy doesn’t increase the risk of preterm birth, cesarean delivery, or low birth weight of the babies. Complete vaccination against tcovid-19 declines the risk of hospital admission for severe disease and pneumonia in women.